2003
DOI: 10.1053/ejvs.2002.1891
|View full text |Cite
|
Sign up to set email alerts
|

Outcome following surgery for thoracic outlet syndrome

Abstract: surgery remains an effective tool in the management of TOS. A simple patient-directed questionnaire as used in this study could assist in the standardisation of outcome assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 25 publications
(24 reference statements)
0
27
0
1
Order By: Relevance
“…Most have used subjective outcomes or nonvalidated tools. [19][20][21][22] Reported negative predictors of surgical success for nTOS surgery have included poorly systematized neurologic symptoms, extended resection of the first rib, severe postoperative complications, workers compensation cases, duration of symptoms Ͼ2 years, and previous operations. [22][23][24] Axelrod et al demonstrated an association between psychological and social factors (such as depression, marital status, and education) on outcomes after operative decompression.…”
Section: Discussionmentioning
confidence: 99%
“…Most have used subjective outcomes or nonvalidated tools. [19][20][21][22] Reported negative predictors of surgical success for nTOS surgery have included poorly systematized neurologic symptoms, extended resection of the first rib, severe postoperative complications, workers compensation cases, duration of symptoms Ͼ2 years, and previous operations. [22][23][24] Axelrod et al demonstrated an association between psychological and social factors (such as depression, marital status, and education) on outcomes after operative decompression.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 There have also been some attempts to assess long-term outcomes, these efforts have primarily focused on diffuse measures of patient satisfaction using unvalidated tools. [19][20][21][22] A recent report by Cordobes-Gual et al 23 presented some functional data using the validated DASH instrument on 23 patients, but they included only a single follow-up at approximately 4 to 6 months after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The symptomatic relief was classified as Excellent (relief of all symptoms); Good (relief of the major symptoms with some residue of symptoms); Fair (improvement in some symptoms, but persistence of major ones); and Poor (failure, no significant improvement). The procedure was considered a success if the patient reported an excellent, good or fair result [2,6].…”
Section: Methodsmentioning
confidence: 99%
“…The implicit supposition of TOS is that arterial, venous and nervous structures can be compressed in the thoracic outlet depending on upper limb attitude. Due to lack of uniformity in the definition of TOS, various treatment strategies have been proposed with varying success [1][2][3][4][5][6]. We have used clinically demonstrated attitudinal compression of the axillary (subclavian) artery coinciding with attitude-dependent incapacitating complaints as an indication for resection of the first rib through a transaxillary approach.…”
Section: Introductionmentioning
confidence: 99%